Cultural paradiplomacy institutions and agenda: The case of Rio Grande do Sul, Brazil - Marié, Solène (Civitas: revista de Ciências Sociais, 2018)
This article aims to analise how the Brazilian State of Rio Grande do Sul (RS) projects its distinctive cultural identity internationally. It does so by identifying the cultural elements in the state’s paradiplomacy from 1987 to 2014 through a sequence analysis including two elements: RS’s paradiplomatic and cultural institutions; RS’s paradiplomatic agenda. Three phases are identified in terms of space given to culture in the paradiplomacy institutional framework: expansion (1987-1994); retraction (1995- 2010); expansion (2011-2014). The phases are slightly different in terms of agenda: will but lack of means (1987-1990); focus on other issues (1991-2010); construction of an incipient agenda (2011-2014). Also, the 2012 actions to structure cultural policy at federal and state level can be seen as a factor for the agenda expansion in the last phase. However, despite the discourse around the gaúcha identity being present within the state and country, the projection further afield remains weak. Generally, the multiple changes in institutional framework and agenda show that a long-term project has not been decided on. Thus, the resulting policies are highly dependent on each governor’s vision. ***Instituições e agenda de paradiplomacia cultural: O caso do Rio Grande do Sul*** O objetivo deste artigo é de avaliar como o Estado do Rio Grande do Sul (RS), Brasil, projeta internacionalmente a sua identidade cultural singular. Para tanto, ele busca identificar os elementos culturais na paradiplomacia do estado de 1987 a 2014 com uma análise de trajetória composta de dois elementos: as instituições paradiplomáticas e culturais do RS; a agenda paradiplomática do RS. São identificadas três fases em termos de espaço dado à cultura na estrutura paradiplomática: expansão (1987-1994); redução (1995-2010); expansão (2011-2014). As fases relativas à agenda são um pouco diferentes: ambição, mas falta de meios (1987-1990); foco em outras temáticas (1991-2010); construção de uma agenda incipiente (2011-2014). Além disso, as ações conduzidas em 2012 para estruturar as políticas culturais em nível federal e estadual podem ser vistas como um fator da expansão da agenda na última fase. Entretanto, apesar do discurso ao redor da identidade gaúcha ser presente dentro do estado e em nível nacional, a projeção internacional dele é fraca. De maneira geral, as múltiplas mudanças na estrutura institucional e na agenda mostram que um projeto de longo prazo não foi estabelecido. Portanto, as políticas resultantes são altamente dependentes da visão de cada governador.